Communication Ethics in Social Relationships Using Social Media Wisely in Islamic Values - Solekhan, Muhammad (PT. Riset Press International, 2023)
The facts show that the etiquette of communication on social media needs to be built so that the relationship between netizens on social media can be harmonious and peaceful. This study discusses the etiquette of communication on social media according to an Islamic view and how to build a wise attitude in using social media. This study uses a sociological approach and the method that the authors use in this study uses qualitative methods. Communication ethics in Islam aims to form a wise attitude in social media. This attitude is considered capable of being a shield to guard against quality of information and maintain the stability of the media so as not to lose its direction. Thus, the message does not become a descendant class. The issue of communication manners on social media is regulated in the Al-Quran and Hadith. To build a wise attitude on social media, the following steps can be taken: using kind and polite words, disseminating useful information, not spreading lies or hate speech, correcting misinformation and providing advice.